The Role of the Inter-/Supraspinous Ligament Complex in Stand-Alone Interspinous Process Devices: A Biomechanical and Anatomic Study - Kaulhausen, T.; Siewe, J.; Eysel, P.; Knifka, J.; Notermans, H. P.; Koebke, J.; Sobottke, R. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Lumbar spinal stenosis (LSS) with neurogenic intermittent claudication is one of the most common degenerative spinal diseases in the elderly. For patients over 65 years with LSS, open decompression is the most frequent spinal surgery. One problem associated with decompression surgery is the emergence of instability, which is found in varying grades of severity. For some patients with LSS, interspinous process devices (IPD) may be a viable alternative to open decompression. The purpose of this study is to examine the destruction and changes to the interspinous and supraspinous ligament complex after percutanous IPD implantation.Methods Biomechanical and anatomic assessments were performed on the lumbar spine (L1–L4) of 11 fresh human cadavers. The biomechanical examination assayed the force necessary to disrupt the interspinous-supraspinous ligament complex without and after implantation of an IPD. For the anatomic examination, one lumbar spine was plastinated. Serial 4-mm thick sections were cut in sagittal and horizontal planes. The macroanatomic positioning of the implants was then analysed.Results Biomechanics: The average age of the cadavers was 80.6±10.2 years. The minimum average disrupting forces measured 313.74±113.44 N without and 239.47±63.64 N after IPD implantation, a significant (p<0.018) decrease of an average 23.7%. Anatomy: After posterolateral percutaneous IPD implantation, the posterior third of the interspinous ligament, the supraspinous ligament, the thoracolumbar fascia and paraspinous muscles bordering the inter-/supraspinous ligament complex remained undamaged.Conclusion The implantation of an interspinous “stand-alone” spacer significantly minimises the force necessary to disrupt the ISL/SSL complex. After posterolateral percutaneous IPD implantation, the thoracolumbar fascia and associated musculature, which act in synergy with the ISL/SSL complex to stabilise the vertebral column, remain intact.
Keywords: spinal stenosis; minimally invasive spine surgery; interspinous process device (IPD)